Epistemic inclusion: a key challenge for global RRI - Hub Zwart; Ana Barbosa Mendes; Vincent Blok (Journal of Responsible Innovation)
Ten years after introducing the RRI concept, a reflection on its key ambitions seems called for, now that RRI enters the global arena. This paper focues on the key challenge that RRI is currently facing: epistemic inclusion. From the beginning, there has been the awareness that RRI must be open to multiple voices and perspectives, coming from academia, and also from society at large. Besides representing impressive bodies of knowledge, academic disciplines face knowledge gaps as well and must reach out to other knowledge forms, e.g. practical, experiential, and indigenous knowledge. This paper analyses the challenges involved in epistemic inclusion while outlining viable pathways towards addressing them, based on experiences in European projects as our ‘laboratory'. After discussing interdisciplinarity, participatory research, and epistemic pluralism, while also addressing the academic reward system. Special attention is given to indigenous knowledge as a case study for epistemic pluralism.